The Role of the Hobi Kayu Padang in Developing Talent for Obtaining Business Opportunities - Selvi Zola Fenia; Yeki Candra (International Journal of Social Science and Business, 2022)
Wood artisans have not been able to get business opportunities. Most handicrafts of the HKP community are still used privately, and artisans who try to market their products have been unable to attract the market. The purpose of this study is to analyze the role of the Hobi Kayu Padang (HKP) community in developing the talents of members to obtain opportunities, as well as what are the supporting and inhibiting factors of the Hobi Kayu Padang (HKP) community in developing the talents of members to obtain opportunities. This type of research is qualitative research with a descriptive approach. The research subjects were the chairman and four members of the HKP community. Subjects were taken by purposive sampling. The data collection technique is by observation, interviews, and questionnaires conducted to the chairman and members of the HKP as data supporters. Data analysis consists of data reduction, data presentation, and data leveraging. The result of the research is that the role of the community in developing talent to obtain business opportunities is good, seen from the ability of the community to provide adequate facilities and infrastructure for artisans and help develop and become media interactions. The supporting factors for the Hobi Kayu Padang (HKP) community in obtaining business opportunities are environmental support, self-motivation, and economic benefits. In contrast, the inhibiting factors include shortages, difficulty seeking expert guidance, and a weak funding sector.